Neuronal carbonic anhydrase VII provides GABAergic excitatory drive to exacerbate febrile seizures. (23rd July 2013) - Ruusuvuori, Eva; Huebner, Antje K; Kirilkin, Ilya; Yukin, Alexey Y; Blaesse, Peter; Helmy, Mohamed; Kang, Hyo Jung; El Muayed, Malek; Christopher Hennings, J; Voipio, Juha; Šestan, Nenad; Hübner, Christian A; et al.
<x xml:space="preserve">Abstract</x> Brain carbonic anhydrases (CAs) are known to modulate neuronal signalling. Using a novel CA VII (Car7) knockout (KO) mouse as well as a CA II (Car2) KO and a CA II/VII double KO, we show that mature hippocampal pyramidal neurons are endowed with two cytosolic isoforms. CA VII is predominantly expressed by neurons starting around postnatal day 10 (P10). The ubiquitous isoform II is expressed in neurons at P20. Both isoforms enhance bicarbonate‐driven GABAergic excitation during intense GABAA‐receptor activation. P13–14 CA VII KO mice show behavioural manifestations atypical of experimental febrile seizures (eFS) and a complete absence of electrographic seizures. A low dose of diazepam promotes eFS in P13–P14 rat pups, whereas seizures are blocked at higher concentrations that suppress breathing. Thus, the respiratory alkalosis‐dependent eFS are exacerbated by GABAergic excitation. We found that CA VII mRNA is expressed in the human cerebral cortex before the age when febrile seizures (FS) occur in children. Our data indicate that CA VII is a key molecule in age‐dependent neuronal pH regulation with consequent effects on generation of FS.